PENGARUH KNOWLEDGE MANAGEMENT TERHADAP KINERJA ORGANISASI: DIMEDIASI OLEH INOVASI, DAN IMPLEMENTASI STRATEGI (Studi pada RS Lavalette Malang) - Rofiaty, Rofiaty; Noviyanti, Try; Mulyanto, Angga Dwi (IQTISHODUNA, 2015)
Environmental changes in the era of globalization require companies to be able to increase the levelof competition. Some opinions assess that knowledge is seen as a determinant factor in improving theperformance of the company. The purpose of this study is to debate how the influence of knowledge managementon organizational performance through innovation, and implementation strategies. Lavalette Hospital Malangwas chosen as the object of this study. Questionnaires were distributed by using direct survey method witha total of 176 respondents, and 168 questionnaires returned. Based on the analysis of Partial Least Square(PLS smart 2.0) Research shown that knowledge management influence on innovation and implementation ofthe strategy, however innovation does not affect the performance of the organization. The interesting resultfrom this study is evidence that the innovation effect on organizational performance when in mediation by theimplementation of the strategy. Another finding in this study is the direct influence of knowledge managementon organizational performance is worth less than its impact on organizational performance is mediated by theimplementation of the strategy. These findings indicate that the implementation of the strategy has a crucialrole in optimizing the performance of the organization. These results also can be a proliferation of how acompany should realize the optimal organizational performance.